A Foucauldian governmentality analysis of security sector reform in Tunisia - Keskes, Hanen (2023)
This thesis adopts Foucauldian genealogical governmentality as a conceptual framework for the examination of the concept of Security Sector Reform (SSR), and for empirical investigation into the effects of SSR practice on security and democratic reform in post-revolutionary Tunisia. This thesis broadly defines governmentality as the conduct of oneself and others’ conduct through productive – rather than repressive – power. It applies a four-level analytical framework to operationalise governmentality, enabling a critical examination of SSR’s rationalities, technologies, subjectivities, and finalities. This thesis’ application of governmentality challenges the predominant, liberal cosmopolitan-inspired, SSR literature through building on the Foucauldian “discontent with the epistemological and ontological claims inherited from the Enlightenment” which continue to underpin social and political theories (de Larrinaga and Doucet 2010, 2–3). This thesis demonstrates that SSR literature’s liberal cosmopolitan bias poses political and conceptual problems, which ultimately promote blinkered explanatory narratives about SSR’s concept and impact. With a view to overcoming these problems, this thesis demonstrates how genealogical governmentality is the most suitable alternative, critical, perspective which interrogates and historicises the power/knowledge configurations justifying and upholding SSR, without jettisoning an awareness of the agency of the “weak” or the governed. This thesis contributes to and advances the nascent wave of literature applying governmentality research to SSR through the design of a holistic four-level governmentality framework and a tailored interpretivist methodology. Interpretivism is adopted in this thesis as an underlying philosophy as well as a practical approach which dictates the use of specific qualitative methods. This thesis designs and applies a hybrid Critical Discourse Analysis (CDA) model which combines Foucauldian thought regarding the criteria of a Discourse’s formation (Foucault 1991b, 56) with Fairclough’s three dimensional CDA model (Fairclough 1992, 79). This tailored CDA model allows this thesis to undertake an in-depth genealogical analysis of SSR rationalities and epistemological conditions of possibility. Further, CDA is complemented and reinforced in this thesis by qualitative, in-depth, semi structured interviews, as a necessary method for this thesis’ inquiry into SSR’s subjugated knowledges and the subjectivities of various actors within the SSR field. This thesis’ genealogical governmentality analysis denaturalises the SSR concept by revealing the elusiveness of its Discourse. By doing so, this thesis advances a critique of SSR’s impact in Tunisia which transcends the simplistic explanatory narratives which are limited to operational challenges within the recipient countries. Instead, this thesis reveals SSR’s regime of practices as overall exacerbating Tunisia’s security and democratic reform problems. This advances a conceptual and empirical contribution. Conceptually, this thesis challenges problem-solving SSR literature which upholds the positionality of donors and SSR actors as neutral providers of technical assistance, and of SSR as a normative and useful concept going wrong in practice. Empirically, this thesis advances an alternative perspective accounting for the multiplicity of conflicting and competing powers, interests, and perspectives within the security and SSR field in Tunisia. This overcomes the current polarised and contentious discourses inflicting Tunisia’s democratisation path which pit ideological, political, and social groups against each other. Instead, this thesis advances an inclusive and representative diagnosis and vision for security reform, which, as revealed in this research, is essential for successful security reform and, ultimately, democratisation in Tunisia.